The Influence of Creativity, Entrepreneurial Literacy, and Innovation On The Entrepreneurial Interest Of Generation Z In Sukoharjo Regency - Andini, Sekar; Susanti, Ari (EDUCTUM: Journal Research, 2025)
This study aims to examine the influence of entrepreneurial literacy, creativity, and innovation on entrepreneurial interest among Generation Z in Sukoharjo Regency. The type of research used is quantitative with an associative approach. All Generation Z individuals domiciled in Sukoharjo Regency became the study population, with a sample of 100 participants using a purposive sampling method. Data distribution was carried out through questionnaires, while data testing utilized multiple linear regression through SPSS version 25 software. The study findings indicate that creativity has a positive and insignificant effect on entrepreneurial interest among Generation Z in Sukoharjo Regency, entrepreneurial literacy shows a positive and insignificant relationship to entrepreneurial interest, on the contrary, innovation contributes positively and significantly to entrepreneurial interest among Generation Z. This shows that although entrepreneurial understanding and creative thinking skills are important, innovation is the most influential aspect in encouraging entrepreneurial interest among Generation Z. Innovation is an indicator of the young generation’s ability to create new values ??and business opportunities that are relevant to technological developments and market needs.